Marketing Communication of PT PLN (Persero) in Improving Electricity Bill Services through Tariff Discount Program - Linda Selviyani; Dini Wahdiyati; Novi Andayani Praptiningsih (Utan Kayu Publishing, 2025)
This research aims to analyze the marketing communication strategy used by PT PLN (Persero) in socializing the discount program to the public. This program is part of an effort to improve services and relief bill payments. This research is based on the marketing communication theory approach which views the message delivery process as key in shaping consumer perceptions and responses to a program or product. The research method uses a descriptive qualitative approach with data collection through interviews, observation, and documentation. The results showed that PLN applies communication channels, such as social media (Instagram, Facebook, and Twitter) as a marketing communication strategy to convey information about the discount program effectively.